Usual care for youth with autism spectrum disorder: Community-based providers’ reported familiarity with treatment practices - Lerner, Matthew D.; Brown, Cynthia E.; Sridhar, Aksheya; Tschida, Jessica E.; Felsman, Peter; Libsack, Erin J.; Kerns, Connor M.; Moskowitz, Lauren J.; Soorya, Latha; Wainer, Allison; Cohn, Elizabeth; Drahota, Amy (Frontiers in Psychiatry, 2022)
Objective: To examine patterns and predictors of familiarity with transdisciplinary psychosocial (e.g., non-pharmacologic) practices for practitioners treating youths with autism spectrum disorder (ASD) in the United States of America. Method: Practitioners (n = 701) from behavioral, education, medical, and mental health backgrounds who worked with youth (ages 7 – 22) with ASD completed the Usual Care for Autism Survey, which assessed provider demographics and self-reported familiarity with transdisciplinary treatment practices for the most common referral problems of ASD. We examined relations between provider-, setting-, and client-level characteristics with familiarity of key groups of the treatment practices (practice sets). Practice sets were identified using exploratory factor analysis (EFA), and demographic predictors of practice subsets were examined using generalized estimating equations (GEE). Results: The EFA yielded a three-factor solution: 1) environmental modifications/antecedent strategies; 2) behavior analytic strategies; and 3) cognitive strategies, with overall familiarity ranked in this order. Medical providers indicated the least familiarity across disciplines. More experience with ASD and treating those with intellectual disabilities predicted greater familiarity with only environmental modifications/antecedent strategies and behavior analytic, but not cognitive strategies. Experience treating low SES clients predicted familiarity with environmental modification and behavior analytic strategies while experience treating high SES clients predicted familiarity with behavior analytic and cognitive strategies. Conclusion: This is the first study to identify transdisciplinary, interpretable sets of practices for treating youth with ASD based on community providers’ reported familiarity. Results highlight factors associated with familiarity with practice sets, which is essential for mapping practice availability, and optimizing training and dissemination efforts for youth with ASD.